2009
DOI: 10.1007/s00330-009-1654-5
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of unenhanced MR mammography (DWI combined with T2-weighted TSE imaging, ueMRM) for the differentiation of mass lesions

Abstract: Sensitivity and specificity of ueMRM in mass lesions equal that of ceMRM. However, a reduced lesion visibility in ueMRM may lead to more false-negative findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
84
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(99 citation statements)
references
References 29 publications
(47 reference statements)
9
84
1
1
Order By: Relevance
“…Conversely, higher ADC values are usually associated with well-differentiated tumors or benign conditions. In keeping with our findings, in previous studies, lower ADC values were reported to be associated with malignant breast tumors rather than benign conditions (35,36). Constantini et al (37) reported an inverse correlation between the tumor grade and ADC values.…”
Section: Balkansupporting
confidence: 92%
“…Conversely, higher ADC values are usually associated with well-differentiated tumors or benign conditions. In keeping with our findings, in previous studies, lower ADC values were reported to be associated with malignant breast tumors rather than benign conditions (35,36). Constantini et al (37) reported an inverse correlation between the tumor grade and ADC values.…”
Section: Balkansupporting
confidence: 92%
“…Use of DWI together with T2-weighted images created a good unenhanced imaging alternative to DCE-MRI in lesion detection and characterization. This method was previously used in some experimental clinical and reader studies and found to be useful for the diagnosis of breast cancer (24)(25)(26)(27). Lastly, Trimboli et al (28) reported 78% sensitivity and 87% specificity for breast cancer detection with unenhanced MRI of 67 women.…”
Section: Discussionmentioning
confidence: 98%
“…Initially, this feature has invented an application area in the differantial diagnosis of the intracranial masses. Then, extended application area including head-neck (3,4,5), breast (6), vertebral column (7), musculoskletal system (8), abdomen and pelvis (9) were appeared in the subsequent years.…”
Section: Introductionmentioning
confidence: 99%